Impact of Proximity of Teachers’ Aides and Support Strategies. Advantages and Disadvantages. (Kairaranga, 2010)
This paper draws on a wider literature review, completed by the author in 2007, about the effectiveness of teachers’ aides (TAs). It discusses the effects of the proximity of TAs on the students with disabilities to whom they are assigned. It also reports on studies where TAs have been trained to support the students to interact with their peers and where TAs have trained students to interact with other students. The advantages and disadvantages of these factors are discussed.